INTEGRASI PRINSIP DASAR PSIKOLOGI DALAM PEMAHAMAN PERILAKU KRIMINAL - Adinda Putri Dewi; Adelia Citra Erlansyah; Nurul Jannah; Wanda Fitri Berliana; Tugimin Supriyadi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Criminal behavior is a complex phenomenon influenced not only by social and economic factors but also deeply rooted in psychological aspects of the individual. In recent decades, psychological approaches have been increasingly integrated to better understand the motivations, thought patterns, and personality dynamics of offenders. This study aims to identify fundamental psychological principles that explain criminal behavior and examine how integrating psychological frameworks can enhance our understanding of deviant actions. The method used is a literature review with a thematic analysis approach, exploring relevant psychological theories such as social learning theory, social control theory, cognitive dissonance, criminal personality theory, and subjective utility in decision-making. The findings reveal that internal factors, including distorted cognitive schemas, low self-control, value misalignment, and learned behaviors from the environment, play a significant role in the formation of criminal behavior. These results suggest that integrating psychological principles not only strengthens the understanding of criminal causation but also opens the door to more individualized and psychologically grounded intervention strategies. This study recommends the broader application of psychological approaches in crime prevention policies and rehabilitation programs to foster a more holistic and effective response to criminal behavior.